Analisis Potensi Perubahan Brand Image Sepatu Kodachi dari Tahun 1975-2024 - Muharam, Bintang Ardiana; Isnaini, Wiwi (Universitas Pembangunan Jaya, 2025)
Despite having a presence in Indonesia for over fifty years, Kodachi faces challenges in building a reputation and recognition comparable to other brands around it. This may be due to poor brand communication, which makes people believe that Kodachi still lacks attention. The focus of this research is on branding strategies that can increase brand awareness and consumer preference, particularly Gen Z. A qualitative approach was used, and data collection methods were employed through interviews, surveys, and observations. The data collected was then analyzed to find the most effective branding strategies. The results of this study are expected to provide strategic recommendations that are applicable to the Kodachi brand. Setting a consistent and relevant tone of voice, optimizing social media platforms as a means of interaction, development of marketing campaigns, implementation of consumer listening mechanisms.